Inhibitory Effect of Endostar on Specific Angiogenesis Induced by Human Hepatocellular Carcinoma - Qing Ye; Shukui Qin; Yanhong Liu; Jundong Feng; Qiong Wu; Wenshu Qu; Xiaojin Yin (Gastroenterology Research and Practice)
To investigate the effect of endostar on specific angiogenesis induced by human hepatocellular carcinoma, this research systematically elucidated the inhibitory effect on HepG2-induced angiogenesis by endostar from 50 ng/mL to 50000 ng/mL. We employed fluorescence quantitative Boyden chamber analysis, wound-healing assay, flow cytometry examination using a coculture system, quantitative analysis of tube formation, and in vivo Matrigel plug assay induced by HCC conditioned media (HCM) and HepG2 compared with normal hepatocyte conditioned media (NCM) and L02. Then, we found that endostar as a tumor angiogenesis inhibitor could potently inhibit human umbilical vein endothelial cell (HUVEC) migration in response to HCM after four- to six-hour action, inhibit HCM-induced HUVEC migration to the lesion part in a dose-dependent manner between 50 ng/mL and 5000 ng/mL at 24 hours, and reduce HUVEC proliferation in a dose-dependent fashion. Endostar inhibited HepG2-induced tube formation of HUVECs which peaked at 50 ng/mL. In vivo Matrigel plug formation was also significantly reduced by endostar in HepG2 inducing system rather than in L02 inducing system. It could be concluded that, at cell level, endostar inhibited the angiogenesis-related biological behaviors of HUVEC in response to HCC, including migration, adhesion proliferation, and tube formation. At animal level, endostar inhibited the angiogenesis in response to HCC in Matrigel matrix.